Proceedings of Seventh Ship Technology and Research (STAR) Symposium - Ship Technology and Research (STAR) Symposium (7th : 1982 : Honolulu, Hawaii); Society of Naval Architects and Marine Engineers (United States) (New York : The Society of Naval Architects and Marine Engineers, 1982)
19